2015
DOI: 10.1146/annurev-matsci-070214-021043
|View full text |Cite
|
Sign up to set email alerts
|

L12-Strengthened Cobalt-Base Superalloys

Abstract: The discovery of the γ -Co 3 (Al,W) phase with an L1 2 structure provided Co-base alloys with a new strengthening mechanism, enabling a new class of high-temperature material: Co-base superalloys. This review discusses the current understanding of the phase stability, deformation, and oxidation behaviors of γ single-phase and γ + γ two-phase alloys in comparison with Ni-base γ -L1 2 phase and γ + γ superalloys. Relatively low stacking fault energies and phase stability of the γ phase compared with those in Nib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(55 citation statements)
references
References 76 publications
(122 reference statements)
1
54
0
Order By: Relevance
“…This mechanism is the same as that in the g 0 -Ni 3 Al compound [20,21]. TEM analysis confirmed that slip of ordinary a/2〈1 0 1〉{1 1 1} dislocations through the g-Co SS matrix, rafting of the g 0 precipitates perpendicular to the external compressive stress axis [22] and glide of the superlattice intrinsic and extrinsic stacking faults in the g 0 precipitates [23,24] are the main creep mechanisms of the Co-Al-W base alloys.…”
Section: Introductionsupporting
confidence: 53%
“…This mechanism is the same as that in the g 0 -Ni 3 Al compound [20,21]. TEM analysis confirmed that slip of ordinary a/2〈1 0 1〉{1 1 1} dislocations through the g-Co SS matrix, rafting of the g 0 precipitates perpendicular to the external compressive stress axis [22] and glide of the superlattice intrinsic and extrinsic stacking faults in the g 0 precipitates [23,24] are the main creep mechanisms of the Co-Al-W base alloys.…”
Section: Introductionsupporting
confidence: 53%
“…Coarsening, creep, and rafting behaviors are different in cobalt-based γ/γ superalloys than in nickel-based superalloys: both creep and coarsening rates and precipitate shape and alignment under applied stress are different. These differences arise from a complex interplay of the variations in interfacial energies, misfit strains, and elastic stiffnesses from system to system [6][7][8]. Because these processes occur over long time scales, an understanding of the thermodynamic driving force affecting microstructural evolution should accelerate alloy development.…”
Section: Introductionmentioning
confidence: 99%
“…The ordered γ' (L1 2 )-precipitates phase was reported in Cobalt-based alloys for the first time in 1971 [9]. Subsequently, Sato et al reported new γ' phase Co 3 (Al, W) in 2006 [7], which has accelerated the researchs of Cobalt-based superalloys and renewed the worldwide scientific interest [10][11][12][13]. Currently, several γ' (L1 2 )-precipitates in Cobalt-based alloys, such as tungsten containing Co 3 (Ge, W) [14] and Co 3 (Ga, W) [15], have been discovered and effects of alloying elements B, V, Ti, Cr, Mn, Fe, Ni, Nb, Mo, Ta, Re and Hf in novel Cobalt-based superalloys have also been investigated [7,[16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%